3‐D Deep Electrical Resistivity Tomography of the Major Basin Related to the 2016 Mw 6.5 Central Italy Earthquake Fault. Issue 4 (22nd April 2021) - Sapia, V.; Villani, F.; Fischanger, F.; Lupi, M.; Baccheschi, P.; Pantosti, D.; Pucci, S.; Civico, R.; Sciarra, A.; Smedile, A.; Romano, V.; De Martini, P. M.; et al.
Abstract: We provide the first 3‐D resistivity image of the Pian Grande di Castelluccio basin, the main Quaternary depocenter in the hangingwall of the Mt.Vettore–Mt. Bove normal fault system (VBFS), responsible for the October 30, 2016 Mw 6.5 Norcia earthquake (central Italy). The subsurface structure of the basin is poorly known, and its relation with the VBFS remains debated. Using the recent Fullwaver technology, we carried out a high‐resolution 2‐D transect crossing the 2016 coseismic ruptures coupled with an extensive 3‐D survey with the aim of: (a) mapping the subsurface of the basin‐bounding splays of the VBFS and the downdip extent of intrabasin faults; (b) imaging the infill and pre‐Quaternary substratum down to ∼1 km depth. The 2‐D resistivity section highlights under the coseismic ruptures a main dip‐slip fault zone with conjugated splays. The 3‐D resistivity model suggests that the basin consists of two depocenters (∼300 and ∼600 m deep, respectively) filled with silty sands and gravels (resistivity <300 Ωm), bounded and cross‐cut by NNE‐, WNW‐, and NNW‐trending faults with throws of ∼200–400 m. We hypothesize that the NNE‐trending system acted during the early basin development, followed by NNW‐trending and currently active splays of the VBFS that overprint pre‐existing structures and locally control the infill architecture. Moreover, beneath the basin we detect a shallow NW‐dipping blind fault. The latter is likely a hangingwall splay of the adjacent regional Mts. Sibillini Thrust, which may have been partly involved in the rupture process of the Norcia mainshock. Key Points: We show the first 3‐D shallow resistivity image of the Mw 6.5 Norcia earthquake fault system and its main Quaternary hangingwall basin The mainshock fault system overprints NNE‐ and WNW‐trending faults that promoted the complex evolution of the Castelluccio hangingwall basin We detect two main depocenters, 300 and 500–600 m deep, and a low‐angle fault to the south‐east of the basin, likely related to thrusting